The Impact Of Transaction Security, Ease Of Use, And Service Quality Of Mobile Banking On Customer Satisfaction At Bank NTB Syariah - Nadia, Febriyanti Putri; Dethan , Stevany Hanalyna; Widiyanti, Baiq Dinna; Jati, Lalu Jatmiko; Assa’ady, M. Chothibul Umam (Tractare: Jurnal Ekonomi-Manajemen, 2026)
This study aims to identify and test the influence of transaction security, ease of use, and service quality of mobile banking (m-banking) on customer satisfaction at Bank NTB Syariah. The study employs a quantitative causal-associative approach with a sample of 170 active m-banking users selected using simple random sampling and purposive sampling techniques. Data were collected via a 1–5 Likert scale questionnaire and analyzed using multiple linear regression with SPSS. The results of the study indicate that: (1) transaction security does not have a significant effect on customer satisfaction; (2) ease of use has a significant negative effect; (3) service quality has a significant positive effect and is the most dominant factor; (4) all three variables simultaneously have a significant effect on customer satisfaction. These findings indicate that Bank NTB Syariah customers with high digital literacy consider security to be a basic factor that is already met, while excessive ease of use is perceived as reducing functionality. Efforts to improve customer satisfaction should focus on enhancing service quality, which includes efficiency, system availability, privacy, and security